Pembuatan Biskuit dari Campuran Beras, Jagung, Tepung Tempe dan Implikasinya Terhadap Prediksi Kadaluwarsa - Stella Letizia (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Mixed Foodstuff (BMC) with basic materials such as rice flour,corn flour, and tempeh flour contains high protein content. It may contribute to solving the problem of lack of calories of protein in Indonesia. The objective of this research is to study the effect of storage temperature of -20°C, 5°C, 26-27°C, and 35°C with the packaging of polypropylene (PP) and polyethylene (PE) to the expire date of BMC products. The benefit of this research is to contribute the determination of expire date to the food industries. The method used in this research consists of two stages, namely; the first stage was the preparation of raw material and the preparation of biscuit, and the second stages was the determination of expire date of BMC products based on integration and differential methods, respectively in order to determine the reaction order value and the reaction rate constant value. The result of the research shows that to produce BMC biscuit product that fulfills the Indonesian Standard of Quality (SNI), Polypropylene is better to use to package food productin the storage temperature of 26-27°C in which the expiry date that is obtained from the integration method is 176 days, and from the differential method is 267 days. Meanwhile, Polyethylene is better to use to package food product in the storage temperature of (-20)°C in which the expiry date that is obtained from the integration method is 831 days, and from the differential method is 483 days. The value of activation energy obtained in Polypropylene is 3078.69 cal/mol and in Polyethylene is 504.88 cal/mol. It concludes that Polyethylene has fast reaction rate of deterioration and short length of expiry date. In the storage temperature above 10°C, the integration method is better to use to determine the length of the expiry date because it result a shorter expiry date than the one resulted by the differential method. So it gives consumers a better safety.